Embryonic stem‐like cells from rabbit blastocysts cultured with melatonin could differentiate into three germ layers in vitro and in vivo. Issue 11 (4th October 2016) - Wei, Ruxue; Zhao, Xueming; Hao, Haisheng; Du, Weihua; Zhu, Huabin
SUMMARY: The rabbit is considered an important model animal from which to obtain embryonic stem cells because of the utility of this animal in physiology and reproductive research. Here, we derived rabbit ES‐like (rES‐like) cells from blastocysts of superovulated Japanese white rabbits using culture medium containing 10 −7  M melatonin, 10 ng/mL basic fibroblast growth factor, and 1, 000 IU/mL human leukemia inhibitory factor. This concentration of melatonin had the most significant positive effects on the proliferation inner cell mass‐derived cells (improving rates from 19.97% to 34.57%) and the longevity of passaging rES‐like cells. Melatonin also enhanced the expression of pluripotent genes—including alkaline phosphatase, Pou5f1, Sox2, Klf4, c‐ Myc, Nanog, Line28a, and surface marker proteins—in fifth‐passage rES‐like cells. In vitro, these rES‐like cells could spontaneously differentiate into some somatic cells, such as beating cardiomyocytes; formed embryoid bodies; expressed markers of the three germ layers after differentiation; and formed teratomas after injection into non‐obese diabetic‐severe combined immune deficient (NOD‐SCID) mice. Thus, melatonin helped coax ES‐like cells from rabbit blastocysts, which raises intriguing questions about the relationship between pluripotency and proliferation in rabbit embryonic stem cells. Mol. Reprod. Dev. 83: 1003–1014, 2016 © 2016 Wiley Periodicals, Inc .